Negative electrode material, preparation method thereof and battery
By introducing Mg, Al, and P elements into the silicon oxygen material to form a lithium ion transmission channel, the shortcomings of silicon oxygen material in terms of ratio and cyclic performance are solved, and the processing stability of the material is improved by controlling the element ratio and achieving efficient electrochemical performance improvement.
Patent Information
- Application Number
- CN202311294348.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional graphite negative electrode materials are not sufficient to meet market demand in terms of energy density. Although silicon oxygen materials have high specific capacity, their first Coulomb efficiency is low, their conductivity is poor, and their cycle and rate performance is also poor. The lithium doping leads to degradation of material performance and processing stability problems.
The Mg, Al, and P elements are introduced to form a lithium ion transmission channel through coordination with lithium silicate, which improves the rate performance and cyclic performance of the negative electrode material. By controlling the ratio of Mg, Al, and P, the ratio imbalance is suppressed, the hydrolysis of lithium silicate is reduced, the pH value of the material is reduced, and the processing stability is improved.
The rate performance and cycle stability of the negative electrode material are improved, the pH value of the material is reduced, the stability of the slurry is improved, the settlement and gas production problems are avoided, and it is suitable for large-scale production.
Smart Images

Figure CN119725424A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of negative electrode materials, and in particular, to a negative electrode material and a preparation method thereof, and a battery. Background Art
[0002] As the application of lithium-ion batteries continues to expand and deepen, the requirements for lithium-ion battery performance are also increasing, especially in terms of battery energy density. Traditional graphite negative electrode materials are no longer sufficient to meet the growing market demand. As a high-specific capacity negative electrode material, silicon-oxygen materials have attracted much attention in recent years. The specific capacity of silicon-oxygen materials exceeds 2000mAh / g, but compared with graphite materials, silicon-oxygen materials have low first coulombic efficiency, poor conductivity, and poor cycle and rate performance.
[0003] In order to improve the performance of silicon-oxygen materials, lithium doping is often used to increase the first coulombic efficiency of silicon-oxygen materials. However, lithium doping will change the silicon distribution inside the original silicon-oxygen material, causing silicon aggregation and increasing the silicon grain size by more than 50%, resulting in the degradation of the material's rate performance and cycle performance. In addition, lithium-doped silicon-oxygen materials contain lithium silicates, which have a high alkalinity due to the hydrolysis of lithium silicates. When preparing aqueous slurry, they destroy the polymer binder, causing the slurry to settle, which can easily affect the production of batteries. Summary of the invention
[0004] The present application proposes a negative electrode material and a preparation method thereof, and a battery. The introduction of Mg, Al, and P elements into the negative electrode material can be beneficial to the formation of a lithium ion transmission channel and improve the rate performance and cycle performance of the negative electrode material.
[0005] In a first aspect, the present application provides a negative electrode material, the negative electrode material comprising silicon-based active particles and lithium silicate;
[0006] The negative electrode material also includes doping elements, which include Mg, Al and P. The mass content of Mg element in the negative electrode material is a%, the mass content of Al element in the negative electrode material is b%, and the mass content of P element in the negative electrode material is c%. In the negative electrode material, a, b, and c satisfy the following relationship: 0.3≤(a+b) / c≤1.5, and 0.5≤a+b+c≤10.
[0007] In some embodiments, the silicon-based active particles have a silicon grain size of ≤20 nm.
[0008] In some embodiments, the silicon-based active particles include nano-silicon and / or silicon oxide.
[0009] In some embodiments, the silicon-based active particles include silicon oxide, generally represented by SiO x , where 0 <x≤2。
[0010] In some embodiments, the lithium silicate includes at least one of Li2SiO3, Li2Si2O5, and Li4SiO4.
[0011] In some embodiments, in the negative electrode material, 0.002≤a / b≤2.
[0012] In some embodiments, the mass content of Mg element in the negative electrode material is a%, and 0.03≤a≤0.065.
[0013] In some embodiments, the mass content of Al element in the negative electrode material is b%, and 0.09≤b≤0.55.
[0014] In some embodiments, the mass content of the P element in the negative electrode material is c%, and 0.22≤c≤0.65.
[0015] In some embodiments, the negative electrode material further includes a carbon layer located on at least a portion of the surface of the active material.
[0016] In some embodiments, the carbon layer includes at least one of an amorphous carbon material and a graphitized carbon material;
[0017] In some embodiments, the carbon layer includes an amorphous carbon material, and the amorphous carbon material includes at least one of amorphous carbon, carbon black, and activated carbon.
[0018] In some embodiments, the carbon layer includes a graphitized carbon material, and the graphitized carbon material includes at least one of conductive graphite and graphene.
[0019] In some embodiments, the particle size distribution of the negative electrode material satisfies: 10 ≥1.0μm, 3μm≤D 50 ≤10μm, D 90 ≤25.0μm.
[0020] In some embodiments, the mass content of lithium silicate in the negative electrode material is 30% to 80%.
[0021] In some embodiments, the carbon layer has a thickness of 10 nm to 2000 nm.
[0022] In some embodiments, the mass percentage of carbon element in the negative electrode material is 1% to 50%.
[0023] In some embodiments, the specific surface area of the negative electrode material is 0.1 m 2 / g~50m 2 / g.
[0024] In some embodiments, the tap density of the negative electrode material is 0.5 g / cm 3 ~1.5g / cm 3 .
[0025] In some embodiments, the specific capacity of the negative electrode material is tested in the voltage range of 0 to 1.5 V, the specific capacity of the negative electrode material is A when the cut-off voltage is 0.3 V, the specific capacity of the negative electrode material is B when the cut-off voltage is 0.4 V, and the specific capacity of the negative electrode material is C when the cut-off voltage is 0.5 V, and the following relationship is satisfied: 0.7≤(CB) / (BA)≤1.3.
[0026] In some embodiments, the pH value of the negative electrode material is 9-12.
[0027] In a second aspect, the present application provides a method for preparing a negative electrode material, comprising the following steps:
[0028] The silicon-based active particles are immersed in a phosphoric acid solution for surface modification, and a precursor is obtained by solid-liquid separation;
[0029] A mixture including a precursor, a lithium source, a magnesium source and an aluminum source is heat-treated to obtain a negative electrode material, wherein the negative electrode material includes silicon-based active particles, lithium silicate and doping elements, and the doping elements include Mg, Al and P, wherein the mass content of the Mg element in the negative electrode material is a%, the mass content of the Al element in the negative electrode material is b%, and the mass content of the P element in the negative electrode material is c%. In the negative electrode material, a, b, and c satisfy the following relationship: 0.3≤(a+b) / c≤1.5, and 0.5≤a+b+c≤10.
[0030] In some embodiments, the silicon-based active particles have a silicon grain size of ≤20 nm.
[0031] In some embodiments, the silicon-based active particles include nano-silicon and / or silicon oxide.
[0032] In some embodiments, the silicon-based active particles include silicon oxide SiO x , where 0 <x≤2。
[0033] In some embodiments, the lithium silicate includes at least one of Li2SiO3, Li2Si2O5, and Li4SiO4.
[0034] In some embodiments, in the negative electrode material, 0.002≤a / b≤2.
[0035] In some embodiments, the concentration of the phosphoric acid solution is 0.05 mol / L to 5 mol / L;
[0036] In some embodiments, the immersion treatment time is 2h to 10h;
[0037] In some embodiments, the solid-liquid separation comprises at least one of filtration and centrifugation.
[0038] In some embodiments, the lithium source includes at least one of Li2O, Li2CO3, LiOH, Li, LiH, LiAlH4, and LiBH4.
[0039] In some embodiments, the magnesium source includes at least one of Mg2O, Mg, Mg(OH)2, and MgCl2.
[0040] In some embodiments, the aluminum source includes at least one of Al2O3, Al, Al(OH)3, and AlCl3.
[0041] In some embodiments, the heat treatment is performed at a temperature of 400°C to 900°C.
[0042] In some embodiments, the heat treatment is carried out for a holding time of 2 hours to 12 hours.
[0043] In some embodiments, the heat treatment is performed in a protective atmosphere.
[0044] In some embodiments, the protective atmosphere gas includes at least one of nitrogen, helium, neon, argon and krypton.
[0045] In some embodiments, before immersing the silicon-based active particles in a phosphoric acid solution for surface modification, the method further includes: carbon coating the silicon-based active particles to obtain a silicon-carbon composite, and using the silicon-carbon composite as the silicon-based active particles.
[0046] In some embodiments, after heat-treating the mixture comprising the precursor, the lithium source, the magnesium source, and the aluminum source, the method further comprises: carbon-coating the heat-treated product.
[0047] In some embodiments, the carbon coating process includes a gas phase carbon coating process and / or a solid phase carbon coating process.
[0048] In a third aspect, the present application provides a battery, comprising the negative electrode material or the negative electrode material prepared by the method for preparing the negative electrode material.
[0049] The technical solution of the present application has at least the following beneficial effects:
[0050] First, the negative electrode material provided by the present application introduces Mg, Al, and P elements into the negative electrode material. The divalent Mg, trivalent Al and P elements, and the O element in the lithium silicate are coordinated, which can be conducive to the formation of lithium ion transmission channels, improve the rate performance of the negative electrode material, and control the range of (a+b) / c. The imbalance of the Mg, Al, and P ratios can be suppressed. After doping with Mg, Al, and P, magnesium aluminum phosphate substances and lithium silicates are formed on the surface and / or inside of the silicon-based active particles. The lithium silicate and magnesium aluminum phosphate can form faster and more lithium ion transmission channels, thereby reducing the lithium ion transmission energy barrier; and the introduction of Mg, Al, and P elements can reduce the hydrolysis of lithium silicates, thereby reducing the pH value of the negative electrode material and reducing the damage to the binder in the electrode sheet, which is conducive to improving the processing stability problem of the pre-lithium material. The slurry prepared by the negative electrode material is more stable and not easy to settle or produce gas.
[0051] Secondly, the preparation method of the negative electrode material provided in the present application is as follows: the silicon-based active particles are immersed in a phosphoric acid solution so that phosphate ions are evenly adhered to the surface of the silicon-based active particles, and then the silicon-based active particles are mixed with a lithium source, a magnesium source and an aluminum source and heat-treated. During the heat treatment process, the lithium source and the silicon-based active particles form lithium silicates, and the lithium in part of the lithium silicates is replaced by magnesium and aluminum, and the silicon is replaced by phosphorus. Among them, divalent Mg and trivalent Al have a larger radius than Li, and phosphorus can also provide more bonding points than silicon. When Mg, Al and P, O are coordinated, magnesium aluminum phosphate substances and lithium silicates are formed on the surface and / or inside of the silicon-based active particles. The lithium silicate and magnesium aluminum phosphate can form faster and more lithium ion transmission channels.
[0052] The preparation method of the negative electrode material provided in the present application can not only improve the electrochemical performance of the material, but also be suitable for large-scale production. The prepared negative electrode material can effectively improve the rate performance and cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 A process flow chart of a method for preparing a negative electrode material provided in an embodiment of the present application;
[0054] Figure 2 This is a comparison chart of the cycle performance of the negative electrode materials prepared in Example 1 of the present application and Comparative Example 1;
[0055] Figure 3 Schematic diagram of the cycle capacity retention state of the negative electrode material prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0056] The following is a preferred implementation of the embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the embodiment of the present invention. These improvements and modifications are also considered to be within the scope of protection of the embodiment of the present invention.
[0057] As the application of lithium-ion batteries continues to expand and deepen, the requirements for lithium-ion battery performance are also increasing, especially in terms of battery energy density. Traditional graphite negative electrode materials are no longer sufficient to meet the growing market demand. As a high-specific capacity negative electrode material, silicon-oxygen materials have attracted much attention in recent years. The specific capacity of silicon-oxygen materials exceeds 2000mAh / g, but compared with graphite materials, silicon-oxygen materials have low first coulombic efficiency, poor conductivity, and poor cycle and rate performance.
[0058] In order to improve the performance of silicon-oxygen materials, lithium doping is often used to increase the initial coulombic efficiency of silicon-oxygen materials. However, lithium doping will change the silicon distribution inside the original silicon-oxygen material, causing silicon aggregation, leading to degradation of the material's cycle performance and rate performance, and increased expansion. In addition, lithium-doped silicon-oxygen materials contain lithium silicates, which have a high alkalinity due to the hydrolysis of lithium silicates. When preparing aqueous slurry, they destroy the polymer binder, causing the slurry to settle, which can easily affect the production of batteries.
[0059] Specifically, the present application provides a negative electrode material, the negative electrode material includes an active substance, and the active substance includes silicon-based active particles and lithium silicate;
[0060] The negative electrode material also includes doping elements, which include Mg, Al and P. The mass content of Mg element in the negative electrode material is a%, the mass content of Al element in the negative electrode material is b%, the mass content of P element in the negative electrode material is c%, 0.3≤(a+b) / c≤1.5, and 0.5≤a+b+c≤10.
[0061] The negative electrode material provided by the present application introduces Mg, Al, and P elements into the negative electrode material. The divalent Mg, trivalent Al and P elements, and the O element in the lithium silicate are coordinated, which can be beneficial to the formation of lithium ion transmission channels, improve the rate performance of the negative electrode material, and control the range of (a+b) / c, which can suppress the imbalance of the Mg, Al, and P ratios. After doping with Mg, Al, and P, magnesium aluminum phosphate substances and lithium silicates are formed on the surface and / or inside of the silicon-based active particles. The lithium silicate and magnesium aluminum phosphate can form faster and more lithium ion transmission channels, and reduce the lithium ion transmission energy barrier; and the introduction of Mg, Al, and P elements can reduce the hydrolysis of lithium silicates, reduce the pH value of the negative electrode material, and reduce the damage to the binder in the electrode sheet, which is beneficial to improving the processing stability problem of the pre-lithium material. The slurry prepared by the negative electrode material is more stable and not easy to settle or produce gas.
[0062] In the above technical scheme, (a+b) / c can specifically be 0.3, 0.5, 0.7, 0.8, 0.9, 1.0, 1.2, 1.3, 1.4 or 1.5, etc., and of course it can also be other values within the above range, which are not limited here. When (a+b) / c<0.3, the amount of Mg and Al is too small, and the excess P combines with the pre-lithiation doped Li to form lithium phosphate, resulting in the loss of active lithium ions and the reduction of the first efficiency of the material. When (a+b) / c>1.5, the amount of P is too small, and the excess Mg and Al will excessively combine with Si and O to form magnesium silicate, aluminum silicate and other substances, resulting in silicon loss and a decrease in the specific capacity of the negative electrode material. Therefore, controlling the balance of the ratio of Mg, Al and P is conducive to forming an effective lithium ion transmission channel and improving the first coulombic efficiency and rate performance of the negative electrode material. Preferably, 0.6≤(a+b) / c≤1.2.
[0063] In the above technical solution, the value of a+b+c can be 0.5, 1, 1.5, 2, 3, 4, 5, 6, 7, 8, 9 or 10, and of course it can be other values within the above range, which are not limited here. If the value of a+b+c is too small, it means that the content of the doping element in the negative electrode material is too small, the magnesium aluminum phosphate substances formed on the surface and / or inside the silicon-based active particles are insufficient, the pH value of the material is reduced, and after the negative electrode material is prepared to form a slurry, the slurry stability is reduced.
[0064] In some embodiments, the mass content of Mg element in the negative electrode material is a%, 0.03≤a≤0.065, specifically 0.03%, 0.035%, 0.038%, 0.040%, 0.041%, 0.045%, 0.05%, 0.055%, 0.065%, etc., which is not limited here.
[0065] In some embodiments, the mass content of Al element in the negative electrode material is b%, 0.09≤b≤0.55, specifically 0.09%, 0.095%, 0.1%, 0.12%, 0.15%, 0.2%, 0.25%, 0.35%, 0.39%, 0.40%, 0.42%, 0.50%, 0.55%, etc., which is not limited here.
[0066] In some embodiments, the mass content of P element in the negative electrode material is c%, 0.22≤c≤0.65, and may be 0.22%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6% or 0.65%, etc., which is not limited here.
[0067] In some embodiments, the silicon grain size in the silicon-based active particles is ≤20 nm, and may specifically be 20 nm, 19 nm, 18 nm, 15 nm, 12 nm, 10 nm, 8 nm, 5 nm or 2 nm, etc., which is not limited here.
[0068] In some embodiments, the silicon-based active particles include nano-silicon and / or silicon oxide.
[0069] In some embodiments, the silicon-based active particles include silicon oxide; silicon oxide can be represented by the general formula SiO x (0≤x≤2). It can be a material formed by silicon particles dispersed in SiO2, or a material having a tetrahedral structural unit, in which the silicon atom is located at the center of the tetrahedral structural unit, and the silicon atom and the oxygen atom are located at the four vertices of the tetrahedral structural unit. Silicon oxide can be specifically SiO 0.2 、SiO 0.4 、SiO 0.6 、SiO 0.8 , SiO or SiO 1.2 etc. Preferably, the silicon oxide is SiO.
[0070] In some embodiments, the lithium silicate includes at least one of Li2SiO3, Li2Si2O5, and Li4SiO4. It is understandable that the pre-lithiated silicon-based active particles will produce a certain amount of lithium silicate, most of which are located on the surface and / or inside of the silicon-based active particles, or the silicon-based active particles are dispersed in the lithium silicate.
[0071] In some embodiments, the mass content of Mg element in the negative electrode material is a%, the mass content of Al element in the negative electrode material is b%, and 0.002≤a / b≤2. Specifically, it can be 0.002, 0.005, 0.008, 0.01, 0.02, 0.03, 0.05, 0.1, 0.2, 0.3, 0.5, 0.8, 1, 1.5 or 2, etc., of course, it can also be other values within the above range, which are not limited here. It can be understood that the atomic radius of Mg and Al is larger than that of Li. Mg and Al can occupy the lattice position of Li, which is conducive to the formation of larger ion channels, and the doping reaction activity of Mg is better, which can promote more uniform and effective doping of metal elements. Controlling the a / b ratio within the above range can make Mg 2+ With Al 3+ Balanced doping can be achieved without causing a certain element to occupy too much of the Li lattice space, and the formed magnesium aluminum phosphate and lithium silicate can also be more evenly dispersed on the surface and / or inside of the silicon-based active particles; and the simultaneous addition of Mg and Al can make the grains of the lithium silicate crystals more uniform, thereby improving the lithium ion transmission performance.
[0072] In some embodiments, the negative electrode material further includes a carbon layer located on at least a portion of the surface of the active material.
[0073] In some embodiments, the thickness of the carbon layer is 10 nm to 2000 nm; more specifically, it can be 10 nm, 50 nm, 100 nm, 300 nm, 500 nm, 800 nm, 1000 nm, 1500 nm, 1800 nm or 2000 nm, which is not limited here. Controlling the thickness of the carbon layer is beneficial to improving the lithium ion transmission efficiency, facilitating high-rate charge and discharge of the material, improving the volume expansion of the material, and improving the cycle performance of the negative electrode material.
[0074] In some embodiments, the carbon layer includes at least one of an amorphous carbon material and a graphitized carbon material.
[0075] In some embodiments, the carbon layer includes an amorphous carbon material, and the amorphous carbon material includes at least one of amorphous carbon, carbon black, and activated carbon.
[0076] In some embodiments, the carbon layer includes a graphitized carbon material, and the graphitized carbon material includes at least one of conductive graphite and graphene.
[0077] In some embodiments, the tap density of the negative electrode material is 0.5 g / cm 3 ~1.5g / cm 3 , for example 0.2g / cm 3 , 0.3g / cm 3 , 0.5g / cm 3 , 0.6g / cm 3 , 0.7g / cm 3 , 0.8g / cm 3 , 1.0g / cm 3 , 1.2g / cm 3 etc. Preferably 0.7 g / cm 3 ~1.3g / cm 3 .
[0078] In some embodiments, the particle size distribution of the negative electrode material satisfies: 10 ≥1.0μm, 3μm≤D 50 ≤10μm, D 90 ≤25.0μm.
[0079] Specifically, the average particle size D of the negative electrode material 50 It can be 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm or 10μm, etc. The particle size D of the negative electrode material 10It can be 1.0μm, 1.5μm, 2.0μm, 2.5μm, 2.9μm or 3μm, etc. The particle size D of the negative electrode material 90 It can be 25 μm, 20 μm, 18 μm, 15 μm, 12 μm or 10 μm, etc., which is not limited here. Controlling the particle size of the negative electrode material within the above range is beneficial to improving the cycle performance and rate performance of the negative electrode material.
[0080] In some embodiments, the specific surface area ratio of the negative electrode material is 0.1 m 2 / g~50m 2 / g. Optionally, the specific surface area ratio of the composite negative electrode material can be 1m 2 / g, 5m 2 / g, 8m 2 / g, 10m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g, 30m 2 / g, 35m 2 / g, 40m 2 / g, 45m 2 / g or 50m 2 / g, etc., are not limited here; it can be understood that controlling the specific surface area within the above range is beneficial to reducing the consumption of irreversible active lithium ions and improving the first coulombic efficiency of the battery.
[0081] In some embodiments, the mass content of carbon in the negative electrode material is 1% to 50%. Specifically, it can be 1%, 5%, 8%, 10%, 15%, 20%, 30%, 35%, 40%, 45% or 50%, etc., which is not limited here. It should be noted that the carbon in the negative electrode material comes from the carbon material in the carbon layer.
[0082] In some embodiments, the mass content of lithium silicate in the negative electrode material is 30% to 80%, specifically 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or 80%, etc., which is not limited here. Pre-lithiation of silicon-based active particles can effectively improve the first coulombic efficiency of the negative electrode material.
[0083] In some embodiments, the lithium silicate is uniformly distributed on the surface and / or inside of the silicon-based active particles, and at least a portion of the lithium silicate is located in the carbon layer.
[0084] In some embodiments, the specific capacity of the negative electrode material is tested in the voltage range of 0 to 1.5 V, the specific capacity of the negative electrode material is A when the cut-off voltage is 0.3 V, the specific capacity of the negative electrode material is B when the cut-off voltage is 0.4 V, and the specific capacity of the negative electrode material is C when the cut-off voltage is 0.5 V, and the following relationship is satisfied: 0.7≤(CB) / (BA)≤1.3; (CB) / (BA) can specifically be 0.7, 0.8, 0.9, 1.0, 1.1, 1.2 or 1.3, etc., and of course it can also be other values within the above range.
[0085] In some embodiments, the pH value of the negative electrode material is 9 to 12, specifically 9, 9.5, 10, 10.5, 11, 11.5 or 12, etc., and of course, it can also be other values within the above range. The slurry prepared by the negative electrode material provided in the present application is more stable and is not easy to settle or produce gas. The present application also provides a method for preparing a composite negative electrode material, such as Figure 1 As shown, the method includes the following steps S10 to S20:
[0086] S10, immersing the silicon-based active particles in a phosphoric acid solution for surface modification, and performing solid-liquid separation to obtain a precursor;
[0087] S20, heat-treating a mixture including a precursor, a lithium source, a magnesium source and an aluminum source to obtain a negative electrode material, wherein the negative electrode material includes silicon-based active particles, lithium silicate and doping elements, wherein the doping elements include Mg, Al and P, the mass content of Mg element in the negative electrode material is a%, the mass content of Al element in the negative electrode material is b%, and the mass content of P element in the negative electrode material is c%. In the negative electrode material, a, b and c satisfy the following relationship: 0.3≤(a+b) / c≤1.5, and 0.5≤a+b+c≤10.
[0088] The present application provides a method for preparing a negative electrode material, which comprises immersing silicon-based active particles in a phosphoric acid solution so that phosphate ions are uniformly adhered to the surface of the silicon-based active particles, and then mixing the silicon-based active particles with a lithium source, a magnesium source and an aluminum source and heat-treating them. During the heat treatment, the lithium source and the silicon-based active particles form lithium silicates, and the lithium in part of the lithium silicates is replaced by magnesium and aluminum, and the silicon is replaced by phosphorus, wherein the divalent Mg and the trivalent Al have a larger radius than Li, and phosphorus can also provide more bonding points than silicon. When Mg, Al and P, O are coordinated, magnesium aluminum phosphate substances and lithium silicates are formed on the surface and / or inside of the silicon-based active particles, and the lithium silicates and magnesium aluminum phosphates can form faster and more lithium ion transmission channels.
[0089] The following is a detailed introduction to this program:
[0090] S10. Immerse the silicon-based active particles in a phosphoric acid solution for surface modification treatment, and perform solid-liquid separation to obtain a precursor.
[0091] In some embodiments, the silicon grains in the silicon-based active particles are ≤ 20 nm, specifically, it can be 20 nm, 19 nm, 18 nm, 15 nm, 12 nm, 10 nm, 8 nm, 5 nm or 2 nm, etc., which are not limited herein.
[0092] In some embodiments, the silicon-based active particles include nano-silicon and / or silicon oxide.
[0093] In some embodiments, the silicon-based active particles include silicon oxide SiO x , where 0 < x ≤ 2; the silicon oxide can specifically be SiO 0.2 , SiO 0.4 , SiO 0.6 , SiO 0.8 , SiO or SiO 1.2 etc. Preferably, the silicon oxide is SiO.
[0094] In some embodiments, the concentration of the phosphoric acid solution is 0.05 mol / L to 5 mol / L, specifically, it can be 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 0.8 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L or 5 mol / L, etc., which are not limited herein.
[0095] In some embodiments, the impregnation treatment time is 2 h to 10 h; specifically, it can be 2 h, 3 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, which are not limited herein.
[0096] In some embodiments, the solid-liquid separation method includes at least one of filtration and centrifugation. Filtration can be vacuum filtration, filter paper filtration, etc.
[0097] S20. Heat-treat a mixture containing the precursor, lithium source, magnesium source and aluminum source to obtain a negative electrode material. The negative electrode material includes silicon-based active particles, lithium silicate and doping elements. The doping elements include Mg, Al and P. The mass content of Mg element in the negative electrode material is a%, the mass content of Al element in the negative electrode material is b%, and the mass content of P element in the negative electrode material is c%. In the negative electrode material, a, b, c satisfy the following relationship: 0.3 ≤ (a + b) / c ≤ 1.5, and 0.5 ≤ a + b + c ≤ 10.
[0098] In some embodiments, the lithium source includes at least one of Li2O, Li2CO3, LiOH, Li, LiH, LiAlH4 and LiBH4.
[0099] In some embodiments, the magnesium source includes at least one of Mg2O, Mg, Mg(OH)2, and MgCl2.
[0100] In some embodiments, the aluminum source includes at least one of Al2O3, Al, Al(OH)3, and AlCl3.
[0101] In some embodiments, the heat treatment temperature is 400°C to 900°C, and the heat treatment time is 2h to 10h; specifically, the heat treatment temperature can be 400°C, 500°C, 600°C, 650°C, 700°C, 750°C, 800°C or 900°C. The heat treatment time can be 2h, 4h, 6h, 8h, 9h or 10h, which is not limited here.
[0102] In some embodiments, the heat treatment is performed in a protective atmosphere;
[0103] In some embodiments, the protective atmosphere gas includes at least one of nitrogen, helium, neon, argon and krypton.
[0104] In some embodiments, the lithium silicate includes at least one of Li2SiO3, Li2Si2O5, and Li4SiO4. It is understandable that the pre-lithiated silicon-based active particles will produce a certain amount of lithium silicate, most of which are located on the surface and / or inside of the silicon-based active particles, or the silicon-based active particles are dispersed in the lithium silicate.
[0105] In some embodiments, the mass content of Mg element in the negative electrode material is a%, the mass content of Al element in the negative electrode material is b%, and 0.002≤a / b≤2. Specifically, it can be 0.002, 0.005, 0.008, 0.01, 0.02, 0.03, 0.05, 0.1, 0.2, 0.3, 0.5, 0.8, 1, 1.5 or 2, etc., of course, it can also be other values within the above range, which are not limited here. It can be understood that the atomic radius of Mg and Al is larger than that of Li. Mg and Al can occupy the lattice position of Li, which is conducive to the formation of larger ion channels, and the doping reaction activity of Mg is better, which can promote more uniform and effective doping of metal elements. Controlling the a / b ratio within the above range can make Mg 2+ With Al 3+ Balanced doping can be achieved without causing a certain element to occupy too much of the Li lattice space, and the formed magnesium aluminum phosphate and lithium silicate can also be more evenly dispersed on the surface and / or inside of the silicon-based active particles; and the simultaneous addition of Mg and Al can make the grains of the lithium silicate crystals more uniform, thereby improving the lithium ion transmission performance.
[0106] In some embodiments, before S10, the method further includes subjecting the silicon-based active particles to a carbon coating process to obtain a silicon-carbon composite, and using the silicon-carbon composite as the silicon-based active particles.
[0107] In some embodiments, after S20, the method further comprises subjecting the heat-treated product to a carbon coating treatment.
[0108] In some embodiments, the carbon coating process includes a gas phase carbon coating process and / or a solid phase carbon coating process.
[0109] When the carbon coating treatment is a gas phase carbon coating treatment, it may specifically include: in a protective atmosphere, using a carbon source gas to perform vapor phase deposition on silicon-based active particles to obtain a composite.
[0110] In some embodiments, the temperature of vapor deposition is 600°C to 1000°C, and the temperature may be 600°C, 700°C, 800°C, 850°C, 900°C, 950°C or 1000°C, etc., which is not limited here. Preferably, the temperature of vapor deposition is 700°C to 900°C.
[0111] In some embodiments, the holding time of the vapor deposition is 0.5 h to 10 h; the holding time can be 0.5 h, 1 h, 3 h, 6 h, 8 h, 9 h or 10 h, etc., which is not limited here. Preferably, the holding time of the vapor deposition is 3 h to 9 h.
[0112] In some embodiments, the carbon source gas includes at least one of alkanes, cycloalkanes, olefins, alkynes and aromatic hydrocarbons. Specifically, the carbon source gas includes at least one of acetylene, methane, benzene, toluene, cyclohexane, ethanol, ethylene and propylene.
[0113] In some embodiments, the concentration of the carbon source gas is 0.1 L / min to 10 L / min; specifically, it can be 0.1 L / min, 0.4 L / min, 0.6 L / min, 0.8 L / min, 1.0 L / min, 2 L / min, 5 L / min, 6 L / min, 8 L / min, 9 L / min or 10 L / min, etc., which are not limited here. A certain concentration of carbon source gas is introduced as a gas source for the carbon material, and after a certain period of heat preservation, the carbon material is deposited on the surface of the silicon-based active particles.
[0114] When the carbon coating treatment is a solid-phase carbon coating treatment, it may specifically include: mixing the silicon-based active particles with the second carbon source, and performing a carbonization treatment to obtain a silicon-carbon composite.
[0115] In some embodiments, the second carbon source includes at least one of sucrose, glucose, polyethylene, polyvinyl alcohol, polyethylene glycol, polyaniline, epoxy resin, phenolic resin, furfural resin, acrylic resin, polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyvinyl chloride and asphalt.
[0116] In some embodiments, the mass ratio of the silicon-based active particles to the second carbon source is (20-100): (10-80). The mass ratio of the silicon-based active particles to the second carbon source can be 20:10, 30:15, 50:60, 80:30, 90:20, 100:10, etc., and of course it can also be other values within the above range, which is not limited here.
[0117] In some embodiments, the temperature of the carbonization treatment is 600°C to 1000°C, and the temperature can be 600°C, 700°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 950°C or 1000°C, etc., which are not limited here. Preferably, the temperature of the carbonization treatment is 700°C to 900°C.
[0118] In some embodiments, the carbonization treatment is kept warm for 0.5 h to 10 h, and specifically can be 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, etc., which are not limited here. Preferably, the carbonization treatment is kept warm for 3 h to 5 h.
[0119] In some embodiments, the carbonization treatment is performed in a protective atmosphere, and the gas of the protective atmosphere includes at least one of nitrogen, helium, neon, argon and krypton.
[0120] In some embodiments, the silicon-carbon composite after the carbon coating treatment is further subjected to at least one of pulverization, sieving and demagnetization; preferably, the composite after the carbon coating treatment is further subjected to pulverization, sieving and demagnetization in sequence.
[0121] It should be noted that whether the carbon coating is performed before step S10 or after step S20, it has little effect on this case, because the carbon layer formed by the coating will not affect the contact between the silicon-based active particles and phosphoric acid, and the phosphoric acid can penetrate the carbon layer and evenly adhere to the surface of the silicon-based active particles. In the subsequent heat treatment process, the lithium source and the silicon-based active particles form lithium silicates, and the lithium in some lithium silicates is replaced by magnesium and aluminum, and the silicon is replaced by phosphorus. Among them, the divalent Mg and trivalent Al have a larger radius than Li, and phosphorus can also provide more bonding points than silicon. When Mg, Al and P, O are coordinated, magnesium aluminum phosphate substances and lithium silicates are formed on the surface and / or inside of the silicon-based active particles. Lithium silicates and magnesium aluminum phosphate can form faster and more lithium ion transmission channels. In addition, after carbon coating treatment, the volume expansion of the material can be further improved, the lithium ion transmission efficiency can be improved, which is conducive to the high-rate charge and discharge of the material and improves the cycle performance of the negative electrode material.
[0122] The embodiment of the present invention further provides a battery, using the negative electrode material provided by the above embodiment of the present invention or the negative electrode material prepared by the preparation method of the negative electrode material provided by the above embodiment of the present invention. The battery provided by the embodiment of the present invention has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion.
[0123] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.
[0124] Example 1
[0125] A method for preparing a negative electrode material comprises the following steps:
[0126] (1) Take 1 kg SiO powder (D 50 =6.3 μm), placed in a tube furnace under nitrogen protection, heated to 900°C, introduced acetylene, kept warm for 3 hours and then cooled to obtain a carbon-coated SiO material;
[0127] (2) 100 g of phosphoric acid and 950 g of water were mixed to obtain a phosphoric acid solution, and the carbon-coated SiO material was immersed in the phosphoric acid solution for 6 h, and then filtered to obtain a precursor;
[0128] (3) 100 g of Li2O, 3 g of MgCl2, and 30.3 g of AlCl3 were mixed with the precursor, and then placed in a box furnace under nitrogen protection, heated to 800° C., kept warm for 4 h, taken out and sieved to obtain the negative electrode material.
[0129] The negative electrode material prepared in the embodiment of the present application includes an active substance and a carbon layer located on at least a portion of the surface of the active substance, wherein the active substance includes silicon-based active particles SiO and lithium silicate.
[0130] The other parameters of the negative electrode materials are shown in Table 1.
[0131] Example 2
[0132] A method for preparing a negative electrode material comprises the following steps:
[0133] (1) Take 1 kg SiO powder (D 50 =6.3 μm), placed in a tube furnace under nitrogen protection, heated to 900°C, introduced acetylene, kept warm for 3 hours and then cooled to obtain a carbon-coated SiO material;
[0134] (2) 100 g of phosphoric acid and 950 g of water were mixed to obtain a phosphoric acid solution, and the carbon-coated SiO material was immersed in the phosphoric acid solution for 6 h, and then filtered to obtain a precursor;
[0135] (3) 100 g of Li2O, 1.5 g of MgCl2, and 21.5 g of AlCl3 were mixed with the precursor, and then placed in a box furnace under nitrogen protection, heated to 800° C., kept warm for 4 h, taken out and sieved to obtain the negative electrode material.
[0136] The negative electrode material prepared in the embodiment of the present application includes an active substance and a carbon layer located on at least a portion of the surface of the active substance, wherein the active substance includes silicon-based active particles SiO and lithium silicate.
[0137] The other parameters of the negative electrode materials are shown in Table 1.
[0138] Example 3
[0139] A method for preparing a negative electrode material comprises the following steps:
[0140] (1) Take 1 kg SiO powder (D 50 =6.3 μm), placed in a tube furnace under nitrogen protection, heated to 900°C, introduced acetylene, kept warm for 3 hours and then cooled to obtain a carbon-coated SiO material;
[0141] (2) 150 g of phosphoric acid and 950 g of water were mixed to obtain a phosphoric acid solution, and the carbon-coated SiO material was immersed in the phosphoric acid solution for 6 h, and then filtered to obtain a precursor;
[0142] (3) 100 g of Li2O, 1.5 g of MgCl2, and 10.5 g of AlCl3 were mixed with the precursor, and then placed in a box furnace under nitrogen protection, heated to 800° C., kept warm for 4 h, taken out and sieved to obtain the negative electrode material.
[0143] The negative electrode material prepared in the embodiment of the present application includes an active substance and a carbon layer located on at least a portion of the surface of the active substance, wherein the active substance includes silicon-based active particles SiO and lithium silicate.
[0144] The other parameters of the negative electrode materials are shown in Table 1.
[0145] Example 4
[0146] A method for preparing a negative electrode material comprises the following steps:
[0147] (1) Take 1 kg SiO powder (D 50 =6.3 μm), placed in a tube furnace under nitrogen protection, heated to 900°C, introduced acetylene, kept warm for 3 hours and then cooled to obtain a carbon-coated SiO material;
[0148] (2) 50 g of phosphoric acid and 950 g of water were mixed evenly to obtain a phosphoric acid solution, and the carbon-coated SiO material was immersed in the phosphoric acid solution for 6 h, and then filtered to obtain a precursor;
[0149] (3) 100 g of Li2O, 1.5 g of MgCl2, and 18 g of AlCl3 were mixed with the precursor, and then placed in a box furnace under nitrogen protection, heated to 800°C, kept warm for 4 hours, and then taken out and sieved to obtain the negative electrode material.
[0150] The negative electrode material prepared in the embodiment of the present application includes an active substance and a carbon layer located on at least a portion of the surface of the active substance, wherein the active substance includes silicon-based active particles SiO and lithium silicate.
[0151] The other parameters of the negative electrode materials are shown in Table 1.
[0152] Example 5
[0153] A method for preparing a negative electrode material comprises the following steps:
[0154] (1) Take 1 kg SiO powder (D 50 =6.3 μm), placed in a tube furnace under nitrogen protection, heated to 900°C, introduced acetylene, kept warm for 3 hours and then cooled to obtain a carbon-coated SiO material;
[0155] (2) 80 g of phosphoric acid and 950 g of water were mixed to obtain a phosphoric acid solution, and the carbon-coated SiO material was immersed in the phosphoric acid solution for 6 h, and then filtered to obtain a precursor;
[0156] (3) 100 g of Li2O, 1 g of MgCl2, and 5 g of AlCl3 were mixed with the precursor, and then placed in a box furnace under nitrogen protection, heated to 800° C., kept warm for 4 h, taken out and sieved to obtain the negative electrode material.
[0157] The negative electrode material prepared in the embodiment of the present application includes an active substance and a carbon layer located on at least a portion of the surface of the active substance, wherein the active substance includes silicon-based active particles SiO and lithium silicate.
[0158] The other parameters of the negative electrode materials are shown in Table 1.
[0159] Example 6
[0160] (1) Take 100g of phosphoric acid and 950g of water and mix them evenly to obtain a phosphoric acid solution. 50 =6.3) was immersed in a phosphoric acid solution for 6 hours, and then filtered to obtain a precursor;
[0161] (2) 100 g of Li2O, 3 g of MgCl2, 30.3 g of AlCl3 and the precursor were mixed, and then placed in a box furnace under nitrogen protection, heated to 800 ° C, kept warm for 4 h, and then taken out and sieved to obtain a mixture;
[0162] (3) 1.5 kg of the mixture and 120 g of asphalt were placed in a VC machine and mixed for 40 min at a speed of 500 rpm. After the material was discharged, it was placed in a high-temperature box furnace and calcined at 800 °C for 6 h. Nitrogen was introduced into the box furnace for protection. The material was naturally cooled to room temperature and the negative electrode material was obtained.
[0163] The negative electrode material prepared in the embodiment of the present application includes an active substance and a carbon layer located on at least a portion of the surface of the active substance, wherein the active substance includes silicon-based active particles SiO and lithium silicate.
[0164] The other parameters of the negative electrode materials are shown in Table 1.
[0165] Example 7
[0166] Different from Example 1, the silicon-based active particles are SiO 0.8 .
[0167] Example 8
[0168] Different from Example 1,
[0169] (3) 100 g of Li2O, 1.3 g of MgO, 23.1 g of Al2O3 and the precursor were mixed, and then placed in a box furnace under nitrogen protection, heated to 800°C, kept warm for 4 hours, taken out and sieved to obtain the negative electrode material.
[0170] Comparative Example 1
[0171] (1) Take 1 kg SiO powder (D 50 =6.3 μm), placed in a tube furnace under nitrogen protection, heated to 900°C, introduced acetylene, kept warm for 3 hours and then cooled to obtain a carbon-coated SiO material;
[0172] (2) 100 g of Li2O and carbon-coated SiO material were mixed, and then placed in a box furnace under nitrogen protection, heated to 800° C., kept warm for 4 h, taken out and sieved to obtain the negative electrode material.
[0173] Comparative Example 2
[0174] (1) 1 kg of SiO powder (D50 = 6.3 μm) was placed in a tube furnace and heated to 900 °C under nitrogen protection, acetylene was introduced, and the mixture was kept warm for 3 h and then cooled to obtain a carbon-coated SiO material;
[0175] (2) 62.5 g of phosphoric acid and 950 g of water were mixed to obtain a phosphoric acid solution, and the carbon-coated SiO material was immersed in the phosphoric acid solution for 6 h, and then filtered to obtain a precursor;
[0176] (3) 100 g of Li2O, 1 g of MgCl2, and 17 g of AlCl3 were mixed with the precursor, and then placed in a box furnace under nitrogen protection, heated to 800°C, kept warm for 4 hours, taken out and sieved to obtain the negative electrode material.
[0177] Comparative Example 3
[0178] (1) 1 kg of SiO powder (D50 = 6.3 μm) was placed in a tube furnace and heated to 900 °C under nitrogen protection, acetylene was introduced, and the mixture was kept warm for 3 h and then cooled to obtain a carbon-coated SiO material;
[0179] (2) 150 g of phosphoric acid and 950 g of water were mixed to obtain a phosphoric acid solution, and the carbon-coated SiO material was immersed in the phosphoric acid solution for 6 h, and then filtered to obtain a precursor;
[0180] (3) 100 g of Li2O, 1.3 g of MgCl2, and 7.5 g of AlCl3 were mixed with the precursor, and then placed in a box furnace under nitrogen protection, heated to 800°C, kept warm for 4 hours, taken out and sieved to obtain the negative electrode material.
[0181] Test method:
[0182] 1) Particle size of negative electrode material:
[0183] The particle size is measured using Mastersizer 3000 laser diffraction technology. When the laser beam passes through the dispersed particle sample, the particle size measurement is completed by measuring the intensity of the scattered light. The data is then used to analyze and calculate the particle size distribution that forms the scattering spectrum. D50: The particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%. Its physical meaning is that particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it also account for 50%. D50 is also called the median diameter or median particle size. D90 particle size, D50 particle size, and D10 particle size are the equivalent diameters (average particle sizes) of the largest particles when the cumulative distribution in the distribution curve is 90%, 50%, and 10%, respectively.
[0184] 2) Testing method for specific surface area of negative electrode material:
[0185] Under constant temperature and low temperature, after measuring the adsorption amount of gas on the solid surface at different relative pressures, the monolayer adsorption amount of the sample is obtained based on the Brownauer-Etter-Taylor adsorption theory and its formula (BET formula), thereby calculating the specific surface area of the material.
[0186] 3) Testing method of tap density:
[0187] Using the Quanta vibrator, weigh a certain amount of sample and vibrate 3000 times at 300 times / min to test the tap density. 4) Silicon micro-particle size test method:
[0188] The XRD peak was measured using a Panalytical X'pert Pro X-ray diffractometer, and then the Si peak in the XRD was fitted and analyzed using the Xpert High Score software to calculate the Si crystallite size.
[0189] 5) Carbon content test method:
[0190] The carbon content was tested by thermogravimetric analysis.
[0191] 6) Test of the mass content of Al, Mg and P in the negative electrode material:
[0192] The ICP method was used to test the content of Al, Mg, and P in the material. Test method: 0.500g of negative electrode material was placed in a clean platinum crucible, and then calcined at 750℃ in a muffle furnace in an air atmosphere for 2 hours to completely remove the carbon element; the cooled calcined residue was fully reacted with 4mL HNO3 and 6mL HF mixed acid, and then the platinum crucible containing the solution was placed on a 350℃ hot plate until the solvent was completely evaporated; after the crucible was cooled, 6mL HCl was added, heated until the residue was completely dissolved, and the volume was fixed to a 100mL plastic volumetric flask; finally, the Al, Mg, and P contents of the material were tested using an ICP spectrometer (Agilent 5800VDVICP-OES).
[0193] After the above tests, the negative electrode materials prepared in Examples 1 to 8 and Comparative Example 1 have sample numbers corresponding to S1 to S8 and R1; the performance parameters of the negative electrode materials are shown in Table 1:
[0194] Table 1
[0195]
[0196]
[0197] 7) Button battery test:
[0198] The negative electrode material, conductive carbon black, and binder (styrene-butadiene rubber and hydroxymethyl cellulose) were prepared into a slurry in a ratio of 75:15:10, uniformly coated on a copper foil and dried to form a negative electrode plate, which was assembled into a button cell in an argon atmosphere glove box. The diaphragm used was a polypropylene microporous membrane, the electrolyte used was 1 mol / L lithium hexafluorophosphate (the solvent was a mixture of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate), and the positive electrode plate used was a metal lithium plate.
[0199] The battery was tested using a BlueDian Xinwei 5V / 10mA battery tester with a voltage of 1.5V and a current of 0.1C. The first coulombic efficiency = first charge specific capacity / first discharge specific capacity.
[0200] 8) Cycle performance test:
[0201] The negative electrode material prepared in the above-mentioned embodiment and comparative example was mixed with graphite in a mass ratio of 15:85 to form a negative electrode material, and then mixed with graphite in a mass ratio of 15:85 to obtain a negative electrode active material, and then the negative electrode active material, conductive carbon black, hydroxymethyl cellulose and styrene-butadiene rubber were mixed uniformly in a mass ratio of 92:4:2:2, and coated on a copper foil to prepare a negative electrode sheet, a metal lithium sheet was used as a positive electrode sheet, and polyethylene was used as a separator to prepare a button battery;
[0202] The battery was tested using a BlueDian Xinwei 5V / 10mA battery tester with a voltage of 1.5V and a current of 0.1C. The 50-week cycle retention rate = 50th discharge capacity / first discharge capacity.
[0203] The battery was tested using a BlueDian Xinwei 5V / 10mA battery tester with a voltage of 1.5V and currents of 0.1C and 3C respectively. 3C / 0.1C = discharge capacity at 3C current / discharge capacity at 0.1C current.
[0204] The specific capacity of the negative electrode material was tested in the voltage range of 0 to 1.5V. When the cut-off voltage was 0.3V, the specific capacity of the negative electrode material was A. When the cut-off voltage was 0.4V, the specific capacity of the negative electrode material was B. When the cut-off voltage was 0.5V, the specific capacity of the negative electrode material was C.
[0205] 9) Slurry stability test:
[0206] The negative electrode materials prepared in each embodiment and comparative example were respectively used as active materials, and the negative electrode material, conductive carbon black, and binder (styrene-butadiene rubber and hydroxymethyl cellulose) were prepared into a slurry in a ratio of 75:15:10. The slurry was put into an aluminum-plastic film bag, sealed, and allowed to stand. Then, the shape change of the aluminum-plastic film bag was monitored for a monitoring period of 1 month.
[0207] Table 2 Parameter performance comparison of each battery
[0208]
[0209]
[0210] As shown in Table 2, the negative electrode materials prepared in Examples 1 to 8, the negative electrode materials introduce Mg, Al, and P elements, and the divalent Mg, trivalent Al and P elements, O elements are coordinated, which can be beneficial to the formation of lithium ion transmission channels, improve the rate performance of the negative electrode materials, control the range of (a+b) / c, suppress the imbalance of Mg, Al, and P ratios, and establish effective lithium ion transmission channels; and the introduction of Mg, Al, and P elements can reduce the hydrolysis of lithium silicates, reduce the pH value of the negative electrode materials, and reduce the damage to the binder in the pole piece, which is beneficial to improving the processing stability of the pre-lithium material. The slurry prepared by the negative electrode material is more stable and not easy to settle or produce gas.
[0211] In Example 5, since the value of a+b+c is relatively small, the content of doping elements in the negative electrode material is too small, the magnesium aluminum phosphate substance formed on the surface of the silicon-based active particles is insufficient, the pH value of the material increases, that is, the alkalinity is greater. After the negative electrode material is prepared to form a slurry, the stability of the slurry decreases, and a very small amount of gas production will occur after the storage time increases.
[0212] During the preparation of the negative electrode material of Comparative Example 1, the carbon-coated silicon oxide material is directly pre-lithiated. The lithium-doped silicon oxide material contains lithium silicate. Due to the hydrolysis of lithium silicate, the alkalinity is relatively high. When the aqueous slurry is prepared, the polymer binder is destroyed, resulting in easy sedimentation and gas production of the slurry, and the rate performance and cycle performance of the battery are also significantly reduced.
[0213] The negative electrode material of Comparative Example 2 has an unbalanced ratio of Mg, Al and P, since (a+b) / c>1.5 and a+b+c≤0.5 in the negative electrode material. The amount of P is too small, and the excess Mg and Al will combine excessively with Si and O to form magnesium silicate, aluminum silicate and other substances, resulting in silicon loss and a decrease in the specific capacity of the negative electrode material.
[0214] The negative electrode material of Comparative Example 3 has an unbalanced ratio of Mg, Al and P, since (a+b) / c is less than 0.3 and a+b+c≤0.5 in the negative electrode material, and the amount of Mg and Al is too small. The excess P combines with the pre-lithiation doped Li to form lithium phosphate, resulting in the loss of active lithium ions and the reduction of the initial efficiency of the negative electrode material.
[0215] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.
Claims
1. A negative electrode material, characterized in that: The negative electrode material includes silicon-based active particles and lithium silicate; The negative electrode material further includes doping elements, and the doping elements include Mg, Al and P. The mass content of Mg in the negative electrode material is a%, the mass content of Al in the negative electrode material is b%, the mass content of P in the negative electrode material is c%, and in the negative electrode material, a, b, and c satisfy the following relationship: 0.3≤(a+b) / c≤1.5, and 0.5≤a+b+c≤10.
2. The negative electrode material according to claim 1, characterized in that The negative electrode material includes at least one of the following features (1)-(8): (1) The silicon grain size of the silicon-based active particles is ≤20 nm; (2) The silicon-based active particles include nano-silicon and / or silicon oxide; (3) The silicon-based active particles include silicon oxide, which is generally represented by SiO x , where 0 <x≤2; (4) The lithium silicate includes at least one of Li2SiO3, Li2Si2O5, and Li4SiO4; (5) In the negative electrode material, 0.002≤a / b≤2; (6) The mass content of Mg element in the negative electrode material is a%, and 0.03≤a≤0.065; (7) The mass content of Al element in the negative electrode material is b%, 0.09≤b≤0.55; (8) The mass content of P element in the negative electrode material is c%, and 0.22≤c≤0.
65.
3. The negative electrode material according to claim 1, characterized in that The negative electrode material further includes a carbon layer located on at least a portion of the surface of the active material. The negative electrode material also satisfies at least one of the following characteristics (1)-(11): (1) The carbon layer includes at least one of an amorphous carbon material and a graphitized carbon material; (2) The carbon layer includes an amorphous carbon material, and the amorphous carbon material includes at least one of amorphous carbon, carbon black, and activated carbon; (3) The carbon layer includes a graphitized carbon material, and the graphitized carbon material includes at least one of conductive graphite and graphene; (4) The particle size distribution of the negative electrode material satisfies: D 10 ≥1.0μm, 3μm≤D 50 ≤10μm, D 90 ≤25.0μm; (5) The mass content of lithium silicate in the negative electrode material is 30% to 80%; (6) The thickness of the carbon layer is 10 nm to 2000 nm; (7) The mass content of carbon in the negative electrode material is 1% to 50%; (8) The specific surface area of the negative electrode material is 0.1 m 2 / g~50m 2 / g; (9) The tap density of the negative electrode material is 0.5 g / cm 3 ~1.5g / cm 3 ; (10) The specific capacity of the negative electrode material is tested in the voltage range of 0 to 1.5 V. When the cut-off voltage is 0.3 V, the specific capacity of the negative electrode material is A. When the cut-off voltage is 0.4 V, the specific capacity of the negative electrode material is B. When the cut-off voltage is 0.5 V, the specific capacity of the negative electrode material is C. The following relationship is satisfied: 0.7≤(CB) / (BA)≤1.3; (11) The pH value of the negative electrode material is 9 to 12.
4. A method for preparing a negative electrode material, characterized in that: The steps include: The silicon-based active particles are immersed in a phosphoric acid solution for surface modification, and a precursor is obtained by solid-liquid separation; A mixture including a precursor, a lithium source, a magnesium source and an aluminum source is heat-treated to obtain a negative electrode material, wherein the negative electrode material includes silicon-based active particles, lithium silicate and doping elements, wherein the doping elements include Mg, Al and P, the mass content of the Mg element in the negative electrode material is a%, the mass content of the Al element in the negative electrode material is b%, and the mass content of the P element in the negative electrode material is c%. In the negative electrode material, a, b and c satisfy the following relationship: 0.3≤(a+b) / c≤1.5, and 0.5≤a+b+c≤10.
5. The preparation method according to claim 4, characterized in that: It meets at least one of the following characteristics: (1) The silicon grain size of the silicon-based active particles is ≤20 nm; (2) The silicon-based active particles include nano-silicon and / or silicon oxide; (3) The silicon-based active particles include silicon oxide SiO x , where 0 <x≤2; (4) The lithium silicate includes at least one of Li2SiO3, Li2Si2O5, and Li4SiO4; (5) In the negative electrode material, 0.002≤a / b≤2; (6) The concentration of the phosphoric acid solution is 0.05 mol / L to 5 mol / L; (7) The immersion treatment time is 2h to 10h; (8) The solid-liquid separation includes at least one of filtration and centrifugation.
6. The preparation method according to claim 4, characterized in that: The preparation method satisfies at least one of the following characteristics: (1) The lithium source includes at least one of Li2O, Li2CO3, LiOH, Li, LiH, LiAlH4 and LiBH4; (2) the magnesium source comprises at least one of Mg2O, Mg, Mg(OH)2 and MgCl2; (3) The aluminum source includes at least one of Al2O3, Al, Al(OH)3 and AlCl3; (4) The temperature of the heat treatment is 400° C. to 900° C.; (5) The heat treatment holding time is 2h to 12h; (6) The heat treatment is carried out in a protective atmosphere; (7) The protective atmosphere gas includes at least one of nitrogen, helium, neon, argon and krypton.
7. The preparation method according to claim 4, characterized in that: Before immersing the silicon-based active particles in a phosphoric acid solution for surface modification, the method further includes: performing carbon coating on the silicon-based active particles to obtain a silicon-carbon composite, and using the silicon-carbon composite as the silicon-based active particles.
8. The preparation method according to claim 4, characterized in that: After heat-treating the mixture containing the precursor, the lithium source, the magnesium source and the aluminum source, the method further comprises: carbon coating the heat-treated product.
9. The preparation method according to claim 7 or 8, characterized in that: The carbon coating treatment includes gas phase carbon coating treatment and / or solid phase carbon coating treatment.
10. A battery, characterized in that: The negative electrode material comprises the negative electrode material according to any one of claims 1 to 3 or the negative electrode material prepared by the preparation method according to any one of claims 4 to 9.
Citation Information
Cited By
Negative electrode material and preparation method therefor, and battery
EP4604206A1
Negative electrode material and preparation method therefor, and battery
WO2025066246A1